Integration of Social Activities and Leadership Values in Character Building of Students by the PIJAR Semarang Community - Yola Mutia Damayanti; Mintarsih Arbarini (International Journal of Studies in International Education, 2026)
This study examines the integration of social activities and leadership values in shaping the character of students by the PIJAR Semarang Community as a form of community-based non-formal education. The background of this study stems from the increasing problems with student character, such as low empathy, responsibility, and self-confidence, as well as the increasing cases of violence and bullying in the educational environment. These conditions indicate that formal education has not been fully able to address the challenges of shaping student character. This study uses a qualitative approach with descriptive methods. The research was conducted at the PIJAR Semarang Community by involving community managers, volunteers, and students as research subjects. Data were collected through in-depth interviews, observation of activities, and documentation to obtain a comprehensive understanding of the character-building process. The results of the study show that the PIJAR Semarang Community integrates social activities and leadership values through academic and non-academic learning programs that are designed to be contextual and participatory. Social activities such as play-based learning, social action, field trips, art performances, and leadership training are the main media for instilling character values. The character values developed include responsibility, cooperation, empathy, discipline, and self-confidence. Leadership values are instilled through habit formation, volunteer role models, providing opportunities for participation, and the active involvement of students in every activity. This study also found several obstacles in the form of differences in student character, limited resources, and low self-confidence among some students in leadership. To overcome these obstacles, the PIJAR Semarang Community implemented intensive mentoring, motivation building, and adjustments to activities to make them more inclusive. Overall, this study confirms that the integration of social activities and leadership values in community-based non-formal education plays an important role in the holistic and sustainable character building of students.